A man and his mic: Taking Chris Rock and Dave Chappelle to teacher’s college - Laura Mae Lindo (The European Journal of Humour Research, 2015)
Taking seriously Donnell Rawling’s advice that we need to interrogate our own “inner racism”, this paper begins by examining work on anti-racism in North American education. Arguing that the narratives of diversity, equity, and social justice have paradoxically risen in prominence among educational researchers while their attempts to address equity issues in schools have simultaneously been resisted (Chase 2010), this paper advocates for the continued need to make discourses of race and racism explicit in educational settings (Lindo 2007, 2010, 2015; Solomon & Levine-Rasky 2003; Bell 2009; Earick 2009). To this end, this paper presents and describes the work of “Race Comics” qua anti-racist educators and introduces the benefits of incorporating the comedic material of comedians like Chris Rock and Dave Chappelle in teacher education classrooms. Drawing on personal reflections of this pedagogical strategy in Canadian teacher education classrooms in Ontario (Canada) and Prince Edward Island (Canada), this paper teases out the ways in which these comedic texts in particular provided developing teachers with an opportunity to reflect upon their own normalised racial discourses, highlighting how these interfered with their ability to be the “perfect teacher”. This paper concludes with a discussion of comedy’s ability to help those devoted to developing socially just educational pedagogies to speak freely about their own normalised prejudices. In this way, “the man and his mic” facilitate explicit discussion of social inequities that, as critical race theorists like Derek Bell (1992; 2009) and Gloria Ladson-Billings (1995; 2009a; 2009b) have suggested, ensure that conversations about discourses of race and racism remain central in contemporary discussions about equity.